2005
DOI: 10.1021/es048143z
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Human Antibiotic Substances and Determination of Weekly Mass Flows in Five Sewage Treatment Plants in Sweden

Abstract: Twelve antibiotic substances for human use, including trimethoprim and representatives of the fluoroquinolone (FQ), sulfonamide (SA), penicillin (PE), cephalosporin (CE), nitroimidazole (NI), tetracycline (TC), and macrolide (MA) groups, were subjected to a screening study at five Swedish sewage treatment plants (STPs) during one week in 2002 and one week in 2003. The analytes were extracted from raw sewage water, final effluent, and sludge by solid-phase extraction (SPE) or liquid-solid extraction (as appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
246
4
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 527 publications
(282 citation statements)
references
References 19 publications
29
246
4
3
Order By: Relevance
“…5), suggesting adsorption is an important aqueous removal process for the ARGs and antibiotics at least for ETM-H 2 O and OFX. In fact, previous studies have reported that the predominant removal mechanism for OFX was adsorption onto sludge rather than biodegradation in wastewater treatment plants (Lindberg et al, 2005;Li and Zhang, 2010;Jia et al, 2012). As to ETM-H 2 O, adsorption onto the substrates seems limited when compared to its total mass removals, suggesting biodegradation played a more important role.…”
Section: Discussionmentioning
confidence: 99%
“…5), suggesting adsorption is an important aqueous removal process for the ARGs and antibiotics at least for ETM-H 2 O and OFX. In fact, previous studies have reported that the predominant removal mechanism for OFX was adsorption onto sludge rather than biodegradation in wastewater treatment plants (Lindberg et al, 2005;Li and Zhang, 2010;Jia et al, 2012). As to ETM-H 2 O, adsorption onto the substrates seems limited when compared to its total mass removals, suggesting biodegradation played a more important role.…”
Section: Discussionmentioning
confidence: 99%
“…At pH bellow 7.0, ERY is immediately converted into its main degradation product ERY-H 2 O and ERY is not detected in its original form but as a degradation product (ERY-H 2 O) with an apparent loss of one molecule of water. Thus, ERY-H 2 O is very often quantified in many studies [59], assuming that ERY is totally converted into ERY-H 2 O in SPE procedures. Additionally, since the oral administration of ERY has to pass through strongly acidic conditions in the stomach, the degraded product ERY-H 2 O, does not exhibit the original antibiotic properties [30].…”
Section: Macrolide Antibioticsmentioning
confidence: 99%
“…Other studies did not refer using IS. In some multiresidue studies ENRO [10,24,59] or lomefloxacin [18] were used as ISs. These ISs were suitable because of similarity with the analyzed compounds, but there was a risk about their possible occurrence in the environment.…”
Section: Fluoroquinolone Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, ultrasonic solvent extraction (USE) and solid phase extraction (SPE), because of their simple, fast and inexpensive operational merits, have been adopted extensively as pretreatment techniques to extract and enrich micropollutants from various matrices (Lindberg et al, 2005;Pan et al, 2011a). The analysis of pharmaceuticals in the WWTPs represents a difficult task due to the high complexity of the wastewater and sludge matrices.…”
Section: Introductionmentioning
confidence: 99%